Reliability of MyotonPro in measuring the biomechanical properties of the quadriceps femoris muscle in people with different levels and types of motor preparation - Robert Trybulski; Robert Trybulski; Adrian Kużdżał; Michał Wilk; Jakub Więckowski; Krzysztof Fostiak; Jarosław Muracki (Frontiers Media S.A., 2024)
The aim of this research was to evaluate the reliability of the measurements of biomechanical parameters of the muscles of athletes representing different disciplines as well as untrained people. Ninety-four young, healthy male individuals participated in the study and were divided into five subgroups: footballers (n = 25), volleyballers (n = 14), handballers (n = 19), MMA fighters (n = 16), and undrained group (n = 20). All of the participants underwent measurements of stiffness (S), muscle tone (T) and elasticity (E) by two independent measurers using MyotonPro equipment. Analysis was conducted on two different parts of the quadriceps femoris: rectus femoris (RF) and vastus medialis (VM. Consequently, the comprehensive analysis comprised 564 measurements (94 participants * 3 parameters = 282 * 2 measurers = 564). The results proves high reliability of the myotonometry (Pearson's CC over 0.8208-0.8871 for different parameters, ICC from to 0.74 to 0.99 for different muscles and parameters) excluding only stiffness for the VM which was characterized withlow ICC of 0.08 and relatively highest between the examined parameters MAE% of 8.7% which still remains low value. The most significant differences between the parameters in examined groups were observed between MMA fighters and volleyballers in terms of muscle tone and elasticity of the VM (correlation of 0.14842 and 0.15083 respecitively). These results confirm the usability of myotonometry in measuring the biomechanical properties of the muscles in different sports groups and confirm the independence of the results obtained from the person performing the measurement.